Scleroderma Renal Crisis in Mixed Connective Tissue Disease With Full Renal Recovery Within 3 Months: A Case Report With Expanding Treatment Modalities to Treat Each Clinical Sign as an Independent Entity - Jordana Cheta MD; Suresh Rijhwani MD; Harlan Rust MD (SAGE Publishing, 2017)
Mixed connective tissue disease (MCTD) is a rheumatologic overlap syndrome that can present with symptoms of systemic lupus erythematous, scleroderma, and polymyositis. A severe but rare complication that can occur in MCTD is scleroderma renal crisis. With multiple poor prognostic indicators, the renal outcome is usually poor. The clinical and histological picture is one of a thrombotic microangiopathy. Clinical suspicion has to be high for additional thrombotic or autoimmune processes coexisting due to associated morbidity. In this article, we report a rare case of scleroderma renal crisis in a patient with MCTD who we treated with plasma exchange for clinical suspicion for an underlying thrombotic thrombocytopenia and mycophenolate mofetil for MCTD. The patient had multiple poor prognostic indicators yet made a full renal recovery in less than 3 months.